Diseño De Un Plan De Negocios De La Empresa Mappet (2024)
In Bogotá, the dog identification tag is the most common method for dog recognition, but it has important limitations in terms of safety and effectiveness in recovery in case of loss. This work focuses on the development of a mobile application aimed at improving the identification of lost dogs. To this end, surveys were conducted that identified the shortcomings of current methods and highlighted restrictions in search scope.